2018
DOI: 10.1101/322842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attentional Bias Modification is associated with fMRI Response towards Negative Stimuli in Residual Depression: A Randomized Controlled Trial

Abstract: BackgroundModification of attentional biases (ABM) may lead to more adaptive emotion perception and emotion regulation. Understanding the neural basis of these effects may lead to greater precision for future treatment development. Task-related fMRI following ABM training has so far not been investigated in depression. The main aim of the RCT was to explore differences in brain activity after ABM training in response to emotional stimuli. MethodsA total of 134 previously depressed individuals were randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…No group differences were observed in the opposite contrast or within any other IC’s. Moreover, ABM training was associated with symptom improvement, compared to the placebo training condition, as previously reported (Hilland et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…No group differences were observed in the opposite contrast or within any other IC’s. Moreover, ABM training was associated with symptom improvement, compared to the placebo training condition, as previously reported (Hilland et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…However, in a task-based functional magnetic resonance imaging (fMRI) study Browning et al (2010b) reported that single session ABM was associated with lateral prefrontal cortex (PFC) reactivity towards emotional stimuli in healthy individuals, indicating moderation of neurocircuitry involved in emotion processing after ABM. In a recent study by our group we used a classical emotion regulation fMRI experiment, and found that ABM over 2 weeks was associated with reduced amygdala and anterior cingulate cortex (ACC) activation for negative images (Hilland et al, 2018). Moreover, we reported an improvement in depression symptoms after ABM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…*Since at least 17 experiments provide sufficient power for statistical analysis, some subanalyses were not performed. 19 (Fitzgerald et al, 2017b) Non-significant results 20 (Schmitt et al, 2016) Non-significant results 21 (Light et al, 2011) Non-significant results 22 (Yip et al, 2018) Non-significant results 23 (Hilland et al, 2018) Lacking healthy controls 24 Lacking healthy controls Table S1. List of excluded studies with reasons 25 (Contreras-Rodríguez et al, 2020) Lacking healthy controls 26 (Fitzgerald et al, 2019) Lacking healthy controls 27 (Schmitgen et al, 2019) Lacking healthy controls 28 (Gorka et al, 2019) Lacking healthy controls 29 (Klumpp et al, 2017b) Lacking healthy controls 30 (Fonzo et al, 2017b) Lacking healthy controls 31 (Fonzo et al, 2017a) Lacking healthy controls 32 (Klumpp et al, 2017a) Lacking healthy controls 33 (Reinecke et al, 2018) Lacking healthy controls 34 (Klumpp et al, 2017c) Lacking healthy controls 35 (Goldin et al, 2014) Lacking healthy controls 36 (Reinecke et al, 2014) Lacking healthy controls 37 (Brühl et al, 2013) Lacking healthy controls 38 (Goldin et al, 2013a) Lacking healthy controls 39 (Heller et al, 2013) Lacking healthy controls 40 (Goldin et al, 2013b) Lacking healthy controls 41 (Hermann et al, 2009) Lacking healthy controls 42 (Kanske et al, 2015) Non-whole-brain analysis 43 (Rabinak et al, 2014) Non-whole-brain analysis 44 (Kanske et al, 2012) Non-whole-brain analysis 45 (Lang et al, 2012) Non-whole-brain analysis 46 (Erk et al, 2010) Non-whole-brain analysis 47 (Douw et al, 2020) Non-whole-brain analysis 48 (Klumpp et al, 2019) Non-whole-brain analysis 49 (Jacob et al, 2019) Non-whole-brain analysis 50 (Young et al, 2019) Non-whole-brain analysis 51 …”
Section: Resultsmentioning
confidence: 99%
“…This work may have implications for not only how treatment works but examining new methods of treating youth who suffer from TRD. Interventions that reduce the negativity bias and limbic hyperactivity, like attention bias modification, may aid in prolonging the antidepressant effects of ketamine ( 67 ). Neurofeedback may also hold promise for extending intervention effects by training populations with depression to decrease neural hyperactivity ( 68 ).…”
Section: Discussionmentioning
confidence: 99%